Psychometric of the Curiosity and Exploration Inventory-II in Indonesia - Anggi Setyowati; Min-Huey Chung; Ah. Yusuf; Setya Haksama (SAGE Publishing, 2020)
Background: Curiosity is a personality characteristic, which fits with wellbeing and positive functioning. The objective of this study was to assess the construct validity of the Curiosity and Exploration Inventory II (CEI-II) in Indonesia. Design and Methods: The study included 256 undergraduate students who lived in Indonesia, mean age 19.8 years old. The CEI-II measures stretching and embracing using 11 items. The English version of CEI-II was translated into Bahasa. The Cronbach's alpha coefficient and intraclass correlation coefficient (ICC) were addressed to examine internal consistency reliability and the test-retest reliability. To evaluate construct validity, exploratory factor analysis (EFA) was used to assess factor structure and confirmatory factor analysis (CFA) was used to evaluate the structural model fit of the CEI-II Indonesia version. Results: The study showed Cronbach's alpha for the internal consistency of the overall CEI-II Indonesia version was 0.77. The ICC for the test-retest reliability ranged between 0.753-0.829. EFA showed adequate with the Kaiser-Meyer-Olkin value of 0.86 and the Bartlett's test of sphericity was statistically significant. CFA tested the second-order model with two-order factors and showed a model fit. Conclusions: The CEI-II Indonesia version indicated acceptable construct validity to evaluate curiosity in Indonesia.